De l’idéologie, de l’iconologie et du sexe, ou des formes baroques de l’engagement communiste de Michel Vovelle - Pierre Serna (Cahiers d’histoire.)
This article tries to think of the place of sex, sexual practices and sexual history in the polymorphic work of Michel Vovelle, spanning more than forty years of publications, in which the question of intimacy is never far from the political practices and commitment of a historian who has never hidden his membership in the Communist Party. From ideology to iconology, this article sets out the way in which sex is an indicator of the systems of domination, of the construction of hierarchies, but also a factor of subversion and possible form of emancipation.